Variability Studies of POD and Seed Characterstics of Albizia Procera in Chhattisgarh - Tiwari, Sunil Kumar; Dhuria, S S (International Journal of Scientific Research in Biological Sciences, 2018)
Albizia procera is an important agroforestry tree species widely distributed across different agricultural systems of India.. Therefore to identify the best seed source is a big challenge and to understand about the seed morphology, germination and seedling growth of some provenances/ seedsource is an important step in helping identification of suitable provenance for establishment in Chhattisgarh. The present study was conducted in Departmental Nursery to determine the variation in pod and seed characteristics in five provenances namely Bilaspur, Bastar, Korba, Raigarh and Sarguja of Chhattisgarh,India. The studies conducted through the estimation of range, mean, phenotypic and genotypic coefficient of variability, heritability, genetic advance and genetic gain. The present study revealed that highly significant differences among provenances in all studied parameters except pod thickness. Highest variation among provenances in seed traits were observed in seed weight and seed length while seed thickness has the lowest variation. Significant variations were recorded in all the studied parameter. The extent of variation in pod length and seed width was higher as compared to pod width, seed thickness, seed length and no. of seeds per pod, high heritability is recorded in pod length(46.01%), seed width (67.74%), seed thickness (45.00%) so there is scope for considerable genetic gain.